Penyelenggaraan Jaminan Produk Halal Pasca Pengesahan Undang-Undang Cipta Kerja Dan Implikasinya Terhadap Pelaku Usaha Mikro Di Provinsi Banten - Muhammad Abduh; Isti Nuzulul Atiah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The presence of the Job Creation Law in several articles provides provisions and implementation tools in implementing Halal Product Guarantees. Considering this rule is a new rule, it is also necessary to describe the implementation, impact and optimization of BPJP after post-provision in order to convince consumers and micro and small businesses actors to fully implement the provision. This research uses a descriptive qualitative research type. Descriptive qualitative methods adjust opinions between researchers and informants. The results of this research include explaining that the implementation of the Halal Product Guarantee after the Job Creation Law can be seen from the shorter time for inspections, halal testing and determination of fatwas. The Job Creation Law provides for a self-declaring mechanism for micro and small business accompanied by provisions for assistance by Halal Product Process (PPH) assistant. The impact of halal certification for micro business actors in Banten Province is a universal obligation for business actors to carry out halal certification, and the economic impact for many micro business actors in Banten Province is felt by the cheaper certification fees.